Family case of Potocki-Lupski syndrome - L. N. Kolbasin; T. A. Dubrovskaya; G. B. Salnikova; E. N. Solovieva; M. Yu. Donnikov; R. A. Illarionov; A. S. Glotov; L. V. Kovalenko; L. D. Belotserkovtseva (Molecular Cytogenetics, 2024)
Abstract Background Potocki-Lupski syndrome (PTLS, OMIM # 610883) is a rare genetic developmental disorder resulting from a partial heterozygous microduplication at chromosome 17p11.2. The condition is characterized by a wide variability of clinical expression, which can make its clinical and molecular diagnosis challenging. Case presentation We report here a family (mother and her two children) diagnosed with PTLS. When examining children, neurological and psychological (neuropsychiatric) manifestations (speech delay, mild mental retardation), motor disorders, craniofacial dysmorphism (microcephaly, dolichocephaly, triangular face, wide bulging forehead, long chin, antimongoloid slant, "elfin" ears) were revealed. The suspected clinical diagnosis was confirmed by MLPA and CMA molecular genetic testing which revealed the presence of a segmental aneusomy; microduplication in the 17p11.2 region. Conclusions Children with PTLS can have a clinically recognizable and specific phenotype: craniofacial dysmorphism, motor and neurological manifestations, which may implicate a possible genetic disease to the attending physician. Moreover, each child with this syndrome is unique and may have a different clinical picture. The management of such patients requires a multidisciplinary team approach, including medical genetic counseling.